Changes in Incidence of Notifiable Infectious Diseases in China Under the Prevention and Control Measures of COVID-19 - Bizhen Chen; Bizhen Chen; Meiling Wang; Meiling Wang; Xun Huang; Maokun Xie; Liting Pan; Huiwen Liu; Zhenguo Liu; Pengcheng Zhou; Pengcheng Zhou (Frontiers Media S.A., 2021)
Aim: The aim of this study was to analyze the changes in incidence of notifiable infectious diseases in China under the prevention and control measures of COVID-19.Methods: Using descriptive epidemiological methods, data were collected from the official website of the Health Commission of the People's Republic of China, and the prevalence characteristics of notifiable infectious diseases in the country in 2020 were analyzed and compared with the historical data in 2019. Monthly reporting data on influenza and tuberculosis from 2015 to 2019 were also collected.Results: Except for COVID-19, the total number of notifiable infectious diseases cases in 2020 was 6,366,176, a decrease of 41.38% year-on-year compared with 2019. Category B and C notifiable infectious diseases decreased by 14.84 and 54.98% year-on-year, respectively (P < 0.01). The top three incidence rates were influenza (87.63 cases/100,000), hepatitis B (81.36 cases/100,000) and other infectious diarrhea (76.33 cases/100,000). Three types of diseases with the largest decline were influenza (−2,280,502 cases), hand-foot-mouth disease (−1,174,588 cases), and other infectious diarrhea diseases (−275,746 cases). Compared with 2019, respiratory infectious diseases were reported to be in the largest decline in 2020, followed by intestinal infectious diseases, blood-borne and sexually transmitted diseases, natural foci, and insect-borne infectious diseases. The monthly reported incidences of influenza and tuberculosis in 2020 were lower than the average of the previous 5 years.Conclusion: In 2020, the incidence of most notifiable infectious diseases in China showed a downward trend, non-pharmaceutical interventions (NPIs)such as the wearing of masks, frequent hand-washing, more ventilation, less gathering, etc, played an positive role in the prevention and control of respiratory and intestinal infectious diseases. The various public health intervention strategies and measures adopted by China to contain COVID-19 can provide a reference for the prevention and control of infectious diseases in other countries.